2013
DOI: 10.1109/tvcg.2012.163
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Effects of Stereo, Head Tracking, and Field of Regard on a Small-Scale Spatial Judgment Task

Abstract: Abstract-Spatial judgments are important for many real-world tasks in engineering and scientific visualization. While existing research provides evidence that higher levels of display and interaction fidelity in virtual reality systems offer advantages for spatial understanding, few investigations have focused on small-scale spatial judgments or employed experimental tasks similar to those used in real-world applications. After an earlier study that considered a broad analysis of various spatial understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(42 citation statements)
references
References 37 publications
1
39
1
1
Order By: Relevance
“…A larger FOV would have helped users to perform the task, as users often felt that they were smaller than the onboard camera which did not give a proper sense of the scale of the robot. These findings were expected, as prior studies have found that a larger field of view assists users in a number of different tasks [3] [11]. The other problem users had with the HMD was low resolution.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…A larger FOV would have helped users to perform the task, as users often felt that they were smaller than the onboard camera which did not give a proper sense of the scale of the robot. These findings were expected, as prior studies have found that a larger field of view assists users in a number of different tasks [3] [11]. The other problem users had with the HMD was low resolution.…”
Section: Discussionsupporting
confidence: 69%
“…sense of immersion and proprioception [3]. Using head tracking in addition to a head mounted display (HMD) as a means to improve a user's experience in virtual environments has been detailed in prior work, with evaluations of different settings to determine the effects of different HMD configurations being among the more recent work in the area [7] [11].…”
Section: Introductionmentioning
confidence: 99%
“…To compare our results with prior research [3,15], we also looked at the number of enemies killed and the survival times based on only the display mode and the head tracking mode (see Figure 7). We found that people killed most enemies when both head tracking and stereoscopic 3D was present but survival time was slightly more for head tracked (HT) and monoscopic condition.…”
Section: Quantitative Resultsmentioning
confidence: 99%
“…Their results showed that the performance was best with low-display low-interaction fidelity and high-display and high-interaction fidelity. Another experiment involving a spatial judgment task [15] showed that the participants performed better with head-tracking and best performance was achieved when both stereoscopic 3D and head tracking was present. The worst score was achieved with a combination of monoscopic display and no head tracking.…”
Section: Related Workmentioning
confidence: 99%
“…This is a challenge with any data analysis, but when considering the volumes of information involved in big data projects, it becomes even more pronounced. Again, data visualization will only prove to be a valuable tool if the data quality is assured [9]. To address this issue, companies need to have a data governance or information management process in place to ensure the data is clean.…”
Section: Challenges Faced By Visualizationmentioning
confidence: 99%